A Comparative Study of the Art of Jonah/Yunus: Narrative in the Bible and the Qur’an - Afsar, Ayaz (Islamic Studies, 2009)
This article attempts a comparative study of the story of Jonah/Yunus in the bible and the Qur’an. The texts are analysed from a narratological perspective without judging as to which one has a better form or more authoritative account. The aim of the article is to introduce fresh ways of studying the bible and the Qur’an which might be novel for those who are acquainted with their own tradition only. The approach is based on a close reading that notes linguistic structures, patterns and usages. The article begins with a general introduction of the worldviews of the two narratives, moves on to discuss the structure and function of the narratives, goes on to analyse the characterization and closes with some comments on the style and composition which gives them a distinctive colour and shape.